2013
DOI: 10.1186/1471-230x-13-78
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopist specialty is associated with colonoscopy quality

Abstract: BackgroundSome studies have shown that endoscopist specialty is associated with colorectal cancers missed by colonoscopy. We sought to examine the relationship between endoscopist specialty and polypectomy rate, a colonoscopy quality indicator. Polypectomy rate is defined as the proportion of colonoscopies that result in the removal of one or more polyps.MethodsA cross-sectional study was conducted of endoscopists and their patients from 7 Montreal and 2 Calgary endoscopy clinics. Eligible patients were aged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Recent data challenged the quality of colonoscopy by non-gastroenterologists. [44][45][46] Insufficient experience, especially on the detection and resection of subtle-appearing lesions can limit the effectiveness of colonoscopy in preventing CRC. In a study that used administrative data of 14,064 patients from Ontario, Baxter et al 44 found that endoscopist's specialty (non-gastroenterologist) and setting (non-hospitalbased colonoscopy) were likely associated with a greater risk of postcolonoscopy CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data challenged the quality of colonoscopy by non-gastroenterologists. [44][45][46] Insufficient experience, especially on the detection and resection of subtle-appearing lesions can limit the effectiveness of colonoscopy in preventing CRC. In a study that used administrative data of 14,064 patients from Ontario, Baxter et al 44 found that endoscopist's specialty (non-gastroenterologist) and setting (non-hospitalbased colonoscopy) were likely associated with a greater risk of postcolonoscopy CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective study of primary care in Canada along with primary care trends in diverse post-ACA communities across America will substantially augment trial findings and identify ways to maximize ACA protections. Prospective study of specialized care, gastroenterology for colon cancer care [ 59 62 ] and diverse specialist physicians for other health domains will also be needed to fully inform physician supply policies in both countries.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing use of colonoscopy, there also has been increasing variability in the types of providers performing colonoscopies (eg, gastroenterologists, family medicine [FM], internal medicine [IM], general, and colorectal surgeons, as well as physician extenders such as physician assistants) . While studies have found that nongastroenterologist providers can provide safe and cost‐effective colonoscopy, other studies have reported increased risk of complications (particularly for complex colonoscopies), as well as lower adenoma detection rates, exam completion rates, and cecal intubation rates among nongastroenterologists . These poor outcomes may be due in part to lower procedure volumes …”
mentioning
confidence: 99%
“…13 While studies have found that nongastroenterologist providers can provide safe and cost-effective colonoscopy, [14][15][16][17][18][19][20][21][22][23][24] other studies have reported increased risk of complications (particularly for complex colonoscopies), as well as lower adenoma detection rates, exam completion rates, and cecal intubation rates among nongastroenterologists. [25][26][27][28][29][30][31] These poor outcomes may be due in part to lower procedure volumes. 20,21,27,29,[32][33][34] The extent to which providers in different specialties perform colonoscopies in the general population is unknown.…”
mentioning
confidence: 99%